Milovan Milovanović and First Balkan War - Palević, Milan N.; Jerotijević, Zoran B.; Spalević, Žaklina S. (Collection of Papers of the Faculty of Philosophy in Priština, 2014)
The beginning of XX century opened the Balkan question of Turkish presence and finally the release of Christians from centuries of Ottoman rule. Creating the alliance of Balkan states has been hampered because of the conflicting interests in terms of territory by the Turks held under occupation. At that time it was necessary to have a great diplomatic skill and make that these interests are not contradictory. The emergence of Milovan Milovanovic as leader of the Serbian diplomacy in this period was perhaps the key factor in the creation of the Balkan League. This great scholar and diplomat, took on the job which was the essence of issue, which is the convergence of interests between Serbia and Bulgaria. From abroad Milovanovic was trying to secure the support of Russia, which considered then Serbia as the nearest and most loyal allies in the Balkans. Support from Russia and France gave wings to the Milovanovic’s diplomacy. The creation of the Balkan League was "the crown" of Milovanovic’s diplomatic career. Unfortunately, the untimely death of this great Serbian diplomat did not allow him to see the fruits of his labor. In a lightning war, allies expelled Turkey from the Balkans as a great power and demonstrated the power of the unity of the Balkan orthodox peoples.